One-stop shopping as a cause of slotting fees: A rent-shifting mechanism - Stéphane Caprice; Vanessa von Schlippenbach (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2013)
Consumers increasingly prefer to bundle their purchases into a single shopping trip, inducing complementaries between initially independent or substitutable goods. Taking this one-stop shopping behavior into account, we show that slotting fees may emerge as a result of a rent-shifting mechanism in a three-party negotiation framework, where a monopolistic retailer negotiates sequentially with two suppliers about two-part tariff contracts. If the goods are initially independent or sufficiently differentiated, the wholesale price negotiated with the first supplier is upward distorted. This allows the retailer and the first supplier to extract rent from the second supplier. To compensate the retailer for the higher wholesale price, the first supplier pays a slotting fee as long as its bargaining power vis-à-vis the retailer is not too large.
Keywords: L22; L42; 330; One-stop shopping; rent-shifting; slotting fees